KERJA SAMA INDONESIA-MALAYSIA DALAM PERLINDUNGAN TKI DI MALAYSIA TAHUN 2023-2024 - Abdi Fristho Hutasoit; Bella Ayu Anzalia, Halimah, Joy Prana Bangun, Limra GM Nababan, Martua Felix Jonatan Simanullang, Pi (ADMIN: Jurnal Administrasi Negara, 2023)
The aim of this research is to find out how Indonesia-Malaysia will collaborate in protecting migrant workers in Malaysia in 2023-2024. This research uses a qualitative approach, namely using books, articles, magazines, and others as direct data sources which are tools or (documents) as the main data collection method for analyzing data inductively. The results of this research indicate that the implementation of cooperation regarding the protection of Indonesian Migrant Workers (TKI) or PNI in Malaysia carried out by the Indonesian and Malaysian governments is still not running well due to the lack of commitment and structure for the countries carrying out the collaboration and also the lack of knowledge possessed by TKI in the informal sector.